Examining emotion and action patterns within Finnish elite junior ice hockey players - Luojumäki, Reko (2019)
Self-awareness based self-regulation of performance related states can be seen to play a central role in athletic success. According to the Individualised Zones of Optimal Functioning (IZOF; Hanin, 2007), performance related states can be explained in terms of hedonic tone and functionality. Yet, the perception (debilitative or facilitative) of those states is highly individualised and can be sport specific. Therefore, the purpose of this study was to investigate ice hockey players’ perception of action and emotion patterns in relation to performance, indirectly increase self-awareness and suggestively provide strategies for self-regulation.